2015
DOI: 10.1158/0008-5472.can-14-1891
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclic AMP Pathway Is a Sex-Specific Modifier of Glioma Risk in Type I Neurofibromatosis Patients

Abstract: Identifying modifiers of glioma risk in patients with type 1 neurofibromatosis (NF1) could help support personalized tumor surveillance, advance understanding of gliomagenesis and potentially identify novel therapeutic targets. Here we report genetic polymorphisms in the human adenylate cyclase gene ADCY8 which correlate with glioma risk in NF1 in a sex-specific manner, elevating risk in females while reducing risk in males. This finding extends earlier evidence of a role for cAMP in gliomagenesis based on res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…An array comparative genomic hybridization (aCGH) study of plexiform neurofibromas from NF1 patients showed a recurrent somatic 9p21.3 deletion involving the antisense noncoding RNA in the INK4 locus (ANRIL) and an association between a germline SNP rs2151280 resulting in reduced ANRIL transcript levels and the number of plexiform neurofibromas, suggesting that ANRIL expression mediated plexiform neurofibromas susceptibility 42 . Polymorphisms in the adenylate cyclase 8 ( ADCY8 ) gene correlated with glioma risk in NF1 patients in a sex-specific manner, elevating the risk in females and reducing it in males, also strengthening the evidence of a role of cAMP in gliomagenesis in NF1 43 . Further studies utilizing genome-wide approaches including genome-wide sequencing appear promising for identification of modifier genes in NF1.…”
Section: The Nf1 Genementioning
confidence: 78%
See 1 more Smart Citation
“…An array comparative genomic hybridization (aCGH) study of plexiform neurofibromas from NF1 patients showed a recurrent somatic 9p21.3 deletion involving the antisense noncoding RNA in the INK4 locus (ANRIL) and an association between a germline SNP rs2151280 resulting in reduced ANRIL transcript levels and the number of plexiform neurofibromas, suggesting that ANRIL expression mediated plexiform neurofibromas susceptibility 42 . Polymorphisms in the adenylate cyclase 8 ( ADCY8 ) gene correlated with glioma risk in NF1 patients in a sex-specific manner, elevating the risk in females and reducing it in males, also strengthening the evidence of a role of cAMP in gliomagenesis in NF1 43 . Further studies utilizing genome-wide approaches including genome-wide sequencing appear promising for identification of modifier genes in NF1.…”
Section: The Nf1 Genementioning
confidence: 78%
“…Animal models expressing mutant Nf1 , including mouse, Drosophila, and zebrafish, show deregulated cAMP levels in various cell types 5961 . cAMP levels are also altered in human NF1 -associated tumors, including gliomas 43 . There are many other lesser known neurofibromin 1-regulated effectors downstream of RAS, including afadin, adherens junction formation factor (AFDN), ral guanine nucleotide dissociation stimulator (RALGDS), T-cell lymphoma invasion and metastasis 1 (TIAM1), phospholipase C like 1 (PLCL1), and Ras and Rab interactor 1 (RIN1).…”
Section: The Nf1 Proteinmentioning
confidence: 99%
“…Recently, different sex-specific patterns of mRNA expression profiles and somatic mutations in genes that may modify VHL -associated tumour phenotypes have been identified in sporadic RCC 26. Accordingly, sex-specific patterns of somatic gene inactivation and activity in cell signalling pathways have been found in CNS gliomas 27 28. Sex differences could be important in the future treatment approaches, both surgical and pharmacological, and needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, single nucleotide polymorphisms (SNPs) in adenylate cyclase 8 (AC8) were shown to modify the risk for optic pathway gliomas (OPG, brain tumors) in individuals with NF1. 2 These findings revealed one of those confluence points as they not only identified the first genetic modifier of glioma risk in NF1, but also provided the first in-human validation for an oncogenic role of 3 0 -5 0 -cyclic adenosine monophosphate (cAMP) in gliomagenesis. Moreover, and most intriguingly, SNPs in AC8 increased the glioma risk in females while decreasing the risk in males, thus relating the findings to sexual dimorphism in growth regulation by cAMP.…”
mentioning
confidence: 80%